How do vigilance and feeding by common cranes Grus grus depend on age, habitat, and flock size? - Avilés, Jesus M.; Bednekoff, Peter a (Journal of Avian Biology, 2007)
Animals often spend less time vigilant and more time feeding when foraging in larger groups. This group-size effect does not, however, consider if larger groups differ systematically from smaller ones: Large groups could form in different habitats than small groups or be composed of a different mix of ages or classes than small groups. We examined how habitat differences and flock size and composition explain feeding and vigilance rates in common cranes Grus grus, wintering in holm oak Quercus ilex dehesas of Spain. Flock size and composition were related to habitat type in cranes: flocks formed in areas sown with cereal crops were larger than flocks formed in set aside areas. Vigilance rate depended on habitat but decreased with increasing flock size in a similar way across all habitats. Juveniles were less vigilant than adults and showed little change in vigilance with flock size. Vigilance increased and feeding time decreased over months from November through February. Our results show that vigilance is affected by habitat but that the group size effect on vigilance is not the product of differences between habitats in group size or composition.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Cranes; Dehesa; feeding; flock size; holm oak canopy (voyant); vigilance

Time budget and habitat use of the Common Crane wintering in dehesas of southwestern Spain - Avilés, Jesus M. (Canadian Journal of Zoology, 2003)
In many bird species juvenile inexperience drastically reduces their survival, and parents must provide for them. I tested whether time budget and habitat use in adult wintering Common Cranes (Grus grus) in dehesas (pastoral woodland) of western Spain were affected by the presence of juveniles. Juvenile cranes devote less time to vigilance and spend more time feeding than adults in dehesas. Likewise, juveniles are involved in fewer aggressive encounters than adult cranes. Contrary to expectation, adults accompanied by juveniles devoted the same amount of time to vigilance and feeding and had the same intake rate than adults without juveniles in attendance. However, adult cranes with offspring in attendance were involved in more aggressive encounters than adults without juveniles in attendance when both adult groups were involved in large flocks. In contrast, when adults accompanied by juveniles were in small flocks they were involved in fewer aggressive encounters than adults without juveniles. I also detected a differential use of dehesas by adult cranes that was linked to juvenile presence and explained by the vulnerability of juvenile cranes in intraspecific social relationships. Adults with juveniles in attendance preferred dehesas with livestock where flock sizes were smaller than those in dehesas without livestock, and therefore where they might reduce the number of aggressive encounters with other cranes.
doi: 10.1139/z03-105doi: 10.1139/z03-105The following values have no corresponding Zotero field: publisher: NRC Research Press
Keywords: Cranes; Dehesa; feeding (voyant); intake rate; livestock; parental investment; social structure

Habitat selection patterns of common cranes Grus grus wintering in holm oak Quercus ilex dehesas of central Spain: Effects of human management - Díaz, M.; González, E. (Biological Conservation, 1996)
Most of the western European population of common cranes Grus grus spends the winter in Iberian wooded dehesas, a kind of wood-pasture composed of grasslands, cereal croplands and Mediterranean scrub, densely inter- spersed with holm oak trees Quercus ilex in a savanna- like landscape. Three main types of wooded dehesas can be distinguished according to management." grazed dehesas, shrubby dehesas with occasional grazing, and cultivated dehesas without livestock. Cranes depend largely on acorns during winter and mainly select dehesas cultivated with cereals where acorn abundance is not reduced by livestock. Apparent positive effects of livestock on earth- worm abundance, the main alternative food source for cranes, does not compensate for acorn depletion. Thus, any increase in livestock grazing pressure would have a strong impact on European crane populations during their wintering in Spain.
Keywords: common agricultural policy; Cranes; livestock management; winter feeding